An innovative concept of booster for OMNI-Max anchor. (July 2018) - Liu, Jun; Han, Congcong; Zhang, Yuqin; Ma, Yueyuan; Hu, Yuxia
Highlights: An innovative booster concept is put forward to increase the penetration depth of OMNI-Max anchor. The working efficiency of a booster on the penetration depth of the OMNI-Max anchor is investigated by the CFD simulation. A theoretical model is put forward to predict the dynamic installation of the OMNI-Max anchor and hybrid anchors from water to the seabed. Abstract: OMNI-Max anchors are newly developed dynamically installed anchors for deep water mooring systems. However, the final penetration depth of the anchor after its dynamic installation can be limited, especially in a strong soil seabed with high strength gradient, due to its limited release height in water and large contact areas between the anchor flukes and the adjacent soil. To increase the anchor final penetration depth in seabed, an innovative concept of anchor booster is proposed in this paper. The booster, comprised of a cylindrical shaft with three rear fins, is attached to the anchor tail during its dynamic installation and then is retrieved after installation for reuse. The boosters with three different sizes, hence different masses, are designed and tested. Three dimensional computational fluid dynamics (CFD) simulations were conducted to investigate the working efficiency of a booster on the final penetration depth of the OMNI-Max anchor in a strong soil seabed. Moreover, the entire process of the dynamic installation of the hybrid anchors (an OMNI-Max anchor with a booster) from water to seabed is predicted by a theoretical model. The results demonstrate that the booster is beneficial both in improving the directional stability and impact velocity for the OMNI-Max anchor during its free fall in water. Relative to the OMNI-Max anchor, the final penetration depth of a hybrid anchor increases significantly (from 23% to 115%) due to the addition of the booster, which helps the anchor to gain higher holding capacity. This preliminary study is only to prove effectiveness of the booster concept without a complete investigation of the booster. More detailed studies are planned in the pipeline.